2015
DOI: 10.1063/1.4936792
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz harvesting with shape-optimized InAlAs/InGaAs self-switching nanodiodes

Abstract: In this letter, self-switching nanochannels have been proposed as an enabling technology for energy gathering in the terahertz (THz) regime. Such devices combine their diode-like behavior and high-speed of operation in order to generate DC electrical power from high-frequency signals. By using finite-element simulations, we have improved the sensitivity of L-shaped and V-shaped nanochannels based on InAlAs/InGaAs samples. Since those devices combine geometrical effects with their rectifying properties at zero-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The key to understand the DC performance of the SSD lies on the modulation of the n ss inside the N S by the built-in electric field, producing a modification in the D L along the nanochannel. In this way, some authors indicate that the SSD can be understood as a two-dimensional field-effect transistor with gate and drain short circuited where flanges act as a double lateral-gate terminal [28,33]. The principal mechanism that controls the carrier transport of the SSD is explained in terms of the free carriers that can participate in conduction phenomena and travel through the nanochannel [22].…”
Section: Self-switching Diode Working Principlementioning
confidence: 99%
See 3 more Smart Citations
“…The key to understand the DC performance of the SSD lies on the modulation of the n ss inside the N S by the built-in electric field, producing a modification in the D L along the nanochannel. In this way, some authors indicate that the SSD can be understood as a two-dimensional field-effect transistor with gate and drain short circuited where flanges act as a double lateral-gate terminal [28,33]. The principal mechanism that controls the carrier transport of the SSD is explained in terms of the free carriers that can participate in conduction phenomena and travel through the nanochannel [22].…”
Section: Self-switching Diode Working Principlementioning
confidence: 99%
“…For short D L length, low bias is required to turn the SSD on; nevertheless, an important leakage current is present. By modulating the dimensions of the depletion region inside the nanochannel, the L-shape SSDs are found to be suitable for detection of very weak signals, making the SSD concept an important tool in the development of high-frequency integrated circuits since it has been demonstrated that by choosing appropriate geometrical dimensions, the rectification efficiency can be optimized [33,34].…”
Section: Self-switching Diode Working Principlementioning
confidence: 99%
See 2 more Smart Citations
“…[ 10,23 ] For graphene and InAlAs/InGaAs SSDs, an alternate asymmetric “sawtooth” morphology has also been explored. [ 24,25 ] GDs are of particular interest because they can typically rectify up to THz frequencies and are thus relevant to the development of long‐wavelength energy harvesting, THz imaging sensors, and high‐speed signal processing technologies. [ 26 ]…”
Section: Introductionmentioning
confidence: 99%